Acute phase markers in obese children and adolescents with metabolic disorders - Cura Esquivel, Idalia Aracely; Cordero Pérez, Paula; Torres González, Liliana; Muñoz Espinosa, Linda Elsa (2018)
ABSTRACT Introduction. Obesity is a worldwide public health problem and the most common non-communicable chronic disease. It is associated with an increase in inflammatory acute phase proteins and proinflammatory cytokines. Objective. To assess the levels of acute phase proteins in obese children and adolescents with hepatic steatosis and metabolic syndrome. Methodology. Forty-five children with a body mass index ≥ 95th percentile aged 5.0-15.5 years were included. The following acute phase reactants were determined: C-reactive protein, haptoglobin, alpha-2-macroglobulin, and apolipoprotein A-1; besides, an ultrasound was done to assess hepatic steatosis. Results. C-reactive protein levels increased in all patients. Patients with metabolic syndrome also had high levels of apolipoprotein A-1 and haptoglobin. Patients with hepatic steatosis had a significant increase in alpha-2-macroglobulin in addition to high C-reactive protein. Key words: obesity, C-reactive protein, haptoglobins, alpha-2macroglobulins, apolipoprotein A-1.